Off the spectrum : why the science of Autism has failed women and girls - Rippon, Gina (Seal Press, 2025)
"Who comes to mind when you think about an autistic person? It might be yourself, a relative or friend, a public figure, a fictional character, or a stereotyped image. Regardless, for most of us, it's likely to be someone male. Autistic women are systematically under-diagnosed, under-researched, and underserved by medical and social systems--to devastating effects. In Off the Spectrum, cognitive neuroscientist Gina Rippon sheds light on how old ideas about autism leave women behind and how the scientific community must catch up. Generations of researchers, convinced autism was a male problem, simply didn't bother looking for it in women, creating a snowball effect of biased research. To correct this "male spotlight" problem, Rippon outlines how autism presents differently in girls and women--like their tendency to camouflage their autistic traits, or how their intense interests may take a form considered to be more socially acceptable. When autism research studies don't recruit female participants, Rippon argues, it's not only autistic women who are failed; it's the entire scientific community. Correcting a major scientific bias, Off the Spectrum provides a much-needed exploration of autism in women to parents, clinicians, and autistic women themselves"--